Uncertainty Shocks and Financial Crisis Indicators - Nikolay Hristov; Markus Roth (Center for Economic Studies and ifo Institute (CESifo), 2019)
The current paper broadens the understanding of the role played by uncertainty in the context of macroeconomic fluctuations. It focuses on the implications of uncertainty shocks for indicators that tend to precede financial crises. In an empirical analysis we show for a set of four euro area countries that negative uncertainty shocks, while boosting economic activity, are followed by unfavorable reactions of financial crisis indicators. We conclude that standard uncertainty measures contain some useful information on the potential buildup of vulnerabilities in the financial system.
Keywords: D89; C32; E44; G01; 330; uncertainty; crisis indicators; structural macroeconomic shocks; sign restrictions